A new perspective on behavioral inconsistency and neural noise in aging: compensatory speeding of neural communication - Hong, S. L.; Rebec, George V. (Frontiers in Aging Neuroscience, 2012)
This paper seeks to present a new perspective on the aging brain. Here, we make connections between two key phenomena of brain aging: 1) increased neural noise or random background activity; and 2) slowing of brain activity. Our perspective proposes the possibility that the slowing of neural processing due to decreasing nerve conduction velocities leads to a compensatory speeding of neuron firing rates. These increased firing rates lead to a broader distribution of power in the frequency spectrum of neural oscillations, which we propose, can just as easily be interpreted as neural noise. Compensatory speeding of neural activity, as we present, is constrained by the: A) availability of metabolic energy sources; and B) competition for frequency bandwidth needed for neural communication. We propose that these constraints lead to the eventual inability to compensate for age-related declines in neural function that are manifested clinically as deficits in cognition, affect, and motor behavior.